2015
DOI: 10.1016/j.celrep.2014.12.036
|View full text |Cite
|
Sign up to set email alerts
|

The TMAO-Generating Enzyme Flavin Monooxygenase 3 Is a Central Regulator of Cholesterol Balance

Abstract: SUMMARY Circulating levels of the gut microbe-derived metabolite trimethylamine-N-oxide (TMAO) have recently been linked to cardiovascular disease (CVD) risk. Here we performed transcriptional profiling in mouse models of altered reverse cholesterol transport (RCT), and serendipitously identified the TMAO-generating enzyme flavin monooxygenase 3 (FMO3) as a powerful modifier of cholesterol metabolism and RCT. Knockdown of FMO3 in cholesterol-fed mice alters biliary lipid secretion, blunts intestinal cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
323
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(327 citation statements)
references
References 55 publications
1
323
2
1
Order By: Relevance
“…After absorption, TMA is N-oxidized mainly by FMO3 Warrier et al, 2015). Congenital absence of FMO3 leads to "fish odor syndrome," a result of the inability to metabolize TMA; TMA smells like rotting fish .…”
Section: New Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…After absorption, TMA is N-oxidized mainly by FMO3 Warrier et al, 2015). Congenital absence of FMO3 leads to "fish odor syndrome," a result of the inability to metabolize TMA; TMA smells like rotting fish .…”
Section: New Informationmentioning
confidence: 99%
“…However, beginning in 2011, investigators in the Cleveland Clinic and other venues published a series of groundbreaking papers suggesting TMAO formed from dietary TMA-containing nutrients, especially animal products, might, in fact, be the "toxic" metabolite, a prime cause of atherosclerosis (Wang et al, 2011;Koeth et al, 2013;Tang et al, 2013;Jonsson and Bäckhed, 2015;Shih et al, 2015;Troseid et al, 2015;Wang et al, 2015;Warrier et al, 2015). Basically, what these investigators have shown is that the TMA covalently incorporated in lecithin, choline, betaine, or carnitine can be metabolized in gut by bacterial lyases to release TMA, a gas.…”
Section: New Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…257 TMAO is formed from trimethylamine via hepatic flavin mono-oxygenase 3. 258 Mechanistic studies in mice have identified that modulation of flavin mono-oxygenase 3 levels affect TMAO levels and glucose and lipid metabolism, 259,260 further complicating the identification of the precise mechanism by which TMAO affects CVD. The microbiome plays an obligate role in the formation of trimethylamine (from the trimethylamine-containing nutrients choline and carnitine), and antibiotic knockdown studies clearly show that TMAO is not formed in the absence of the microbiome.…”
Section: Effect Of Dietmentioning
confidence: 99%
“…It is also being investigated in other diseases where the aetiology is thought to be related to a perturbance of the gut microbiome, including colorectal cancer [4], diabetes [5] and renal disease [6] as well as being a putative central mediator in cholesterol balance [7]. Described methods for detecting TMAO are centred on the use of liquid chromatographytandem mass spectrometry with multiple reaction monitoring (LC-MS/MS-MRM), often utilising a stable isotopically labelled standard for quantitation [e.g.…”
Section: Introductionmentioning
confidence: 99%